Transitividade e ergatividade em processos materiais em língua portuguesa na perspectiva da linguística sistêmico-funcional - Lima, Lauro Rafael (2017)
This thesis aims to investigate, categorize and nominate an especific Participant of material sentences, which hasn‟t been identified in the transitivity system of the ideational metafunction of systemic-functional grammar (HALLIDAY; MATTHIESSEN, 2014) in confluence with the participants Agent and Middle, belonging to the system of ergativity. This functionalist approach understands language as a system that can be stratified and categorized. In view of this possibility, we believe that the categorization of participants who can compose a sentence represented by a material process is not fixed and finished. Several possibilities can still be explored. In order to accomplish our objective, we analyzed examples that focus on the concept of the subject, according to different authors of grammars of the Portuguese language, such as Macambira (1978), Almeida (2009), Bechara (2010), Câmara Jr. (2011) and Azeredo (2013). We selected a total of 25 processes pointed by these authors with occurrences of instigating analysis that allow different interpretations. These sentences constituted our first corpus. From this, we delimit our second corpus: 68 sentences of these 25 different processes – extracted from works of the main specialists in the study of Portuguese grammar – analyzed in examples derived from the Corpus Brasileiro (Brazilian Corpus) of PUC-SP, verifying such occurrences in relation to a context. The analyzes allowed the separation of verbs into semantic groups of occurrences, contributing to reach the objectives of the research. We believe that, with our research, we have been able to prove the existence of a new participant to possibly occupy a function with material processes, which is distinguished from the roles of Actor, Goal, Scope, Beneficiary and Client. Data analysis shows the trajectory traversed to the definition and characterization of this Participant on the light of the systemic-functional approach. In addition, we believe we have made a significant contribution to the development of the studies in transitivity/ergativity in Portuguese language from a systemic-functional perspective.